Pemberian Layanan Informasi Preventif Tentang Perilaku Bullying Kepada Siswa Kelas VII SMPN - Gracianus Edwin Tue P. Lejap; Enasely Mega Wenyi Rohi; Dhiu Margaretha (Forum Kerjasama Pendidikan Tinggi, 2024)
Bullying behavior is a negative and deviant behavior carried out by someone with the aim of scaring other people around them. Bullying behavior is very identical to the real life of students in the school environment. Students and students are important instruments in practicing this behavior directly with their friends. Bullying behavior has a direct negative impact on many people physically and mentally. This service activity aims to provide information as well as provide an in-depth understanding of the meaning and direct impact of this behavior to class VII students at SMPN 16 Kupang. This implementation method includes a pre-activity stage which contains preparation and coordination of participants. The activity stage contains the implementation of activities which is preceded by the delivery of material, video shows and a discussion process. The supervision stage includes a segment about building commitment between students and girls about things they want to do to avoid bullying behavior. The results obtained from this service activity are that students and girls obtain new information about the importance of preventing bullying behavior both within the school environment and outside the school environment. Part of the agreement between students and students will be carried out by showing tolerance and respect for their friends not only in the classroom but outside the classroom in the hope of avoiding this behavior from continuing to occur in the school environment.